Analisis Deskriptif tentang Tampilan Kinerja Aparatur Sipil Negara di Sekretariat Pemerintah Kota Kupang Nusa Tenggara Timur Indonesia - Fellyanus Habaora; Jefirstson Richset Riwukore; Tien Yustini (Universitas Indo Global Mandiri)
The purpose of this research was to determine the performance of state civil servants at the Secretariat of the Government of Kupang City, East Nusa Tenggara, Indonesia through the effectiveness of performance indicators, namely quantity, quality, timeliness, cooperation, and self-quality. The research was conducted for 6 months, namely September 2019-February 2020. The total population and research sample were 370 ASN which were determined by purposive stratified proportional sampling based on the position, class, and rank of the ASN. The type of data used is primary data and secondary data obtained by means of questionnaires, observation, and documentation. Data analysis was carried out on performance indicators using descriptive analysis based on the average value of the Likert scale classification. The results showed that in general, the performance of ASN in the Regional Secretariat of the Kupang City Government was effective as indicated by the average performance score of 3.71 or high. This result is because the performance indicators show the results of high-value categories which include quantity (3.79), quality (3.71), timeliness (3.67), cooperation (3.70), and self-quality (3.69).Keywords: quantity, quality, timeliness, cooperation, self-quality, performance